The effect of tourism expenditure on the economy : a new evidence - Norma Azuli Mohd Nor; Norlida Hanim Mohd Salleh; Falatehan, A Faroby (Penerbit Universiti Kebangsaan Malaysia, 2021)
The aim of this study is to evaluate the impact of development on the Malaysian economy through the impact of tourist expenditure by using the Social Accounting Matrix (SAM). The discussion of the study focused on the value of multipliers, factors of production and household income from tourism activities in urban and rural areas. The results had shown that tourist expenditure on the arts, entertainment and recreation subsectors produced the largest multiplier effect on output. Meanwhile, other sub-sectors such as shopping, food and beverage, accommodation and transportation did not show significant differences. In addition, there is a large income distribution gap in urban and rural areas although income distribution to factors of production and households has a positive effect. This inequality needs to be addressed to ensure that tourism development can benefit the overall economy. Among the steps that can be done is Community -Based Tourism (CBT) which involves collaboration between local communities and stakeholders to support authenticity, environmental sustainability, and strengthen management and supervision. It is expected to overcome the problems encountered as a result of the findings of the study. This is expected to increase the positive economic impact of tourism development.